Assessment of the Benefit of a Deep Cleansing Gel Containing Salicylic Acid 2%, Zinc Gluconate 0.2% and Lipohydroxy Acids 0.05% in Patients with Mild to Moderate Truncal Acne: Results from an Exploratory Study - Towersey L; Correia P; Fajgenbaum Feiges M; Euzébio Gonçalves Junior J; Sant'Anna B; Kerob D; Le Floc'h C (Dove Medical Press, 2023)
Loan Towersey,1 Priscila Correia,2 Mariana Fajgenbaum Feiges,2 José Euzébio Gonçalves Junior,2 Beatriz Sant'Anna,3 Delphine Kerob,4 Caroline Le Floc'h4 1Dermatology Department, Carlos Tortely Hospital, Niterói, Rio de Janeiro, Brazil; 2Scientific Expertise, L'Oreal Brazil, Rio de Janeiro, Rio de Janeiro, Brazil; 3Scientific Department, ACD L'Oreal, Paris, France; 4International Scientific Affairs, La Roche-Posay Laboratoire Dermatologique, Levallois-Perret, FranceCorrespondence: Priscila Correia, Scientific Expertise, L'Oreal Brazil, Rio de Janeiro, Rio de Janeiro, Brazil, Tel +55 21 4505-6200, Email priscila.correia@loreal.comPurpose: Acne is a skin condition of the pilosebaceous unit that affects mainly the face, chest and trunk. Approximately 50% of subjects with facial acne also have acne of the trunk. This study investigated the clinical benefit of a cleansing gel containing salicylic acid 2%, zinc gluconate 0.2% and lipohydroxy acid 0.05% in truncal acne after 84 days of daily use.Materials and Methods: A single center, open label, non-randomized study with 51 subjects with mild to moderate truncal acne was conducted. Thirty-five (35) subjects completed the study; mean age was 23 years. Inflammatory and non-inflammatory lesions, Transepidermal water loss (TEWL) and local tolerance were assessed at baseline, Day 42 and Day 84 and total lesion count was calculated.Results: The total lesion count was significantly reduced (p< 0.05) after 42 days (− 21.5%) and 84 days (− 56.3%). Non-inflammatory lesions were significantly decreased after 84 days (− 64.0%) only, while inflammatory lesions were decreased at Day 42 (− 29.2%), and Day 84 (− 48.2%). A statistically significant skin barrier improvement was observed at Day 84 (− 21.26%). No adverse events or relevant local intolerance were reported.Conclusion: The use of the cleansing gel studied was effective in improving mild to moderate truncal acne and contributed to the skin barrier improvement. The product was well tolerated.Clintrial Data Base Identifier: NCT05584150.Keywords: acne, truncal acne, deep cleansing gel, lipo hydroxy acids, LHA, salicylic acid, zinc gluconate